2018
DOI: 10.3892/mmr.2018.9722
|View full text |Cite
|
Sign up to set email alerts
|

Sphingomyelin synthase 1 regulates the epithelial‑to‑mesenchymal transition mediated by the TGF‑β/Smad pathway in MDA‑MB‑231 cells

Abstract: Breast cancer is the most common cancer in women and a leading cause of cancer-associated mortalities in the world. Epithelial-to-mesenchymal transition (EMT) serves an important role in the process of metastasis and invasive ability in cancer cells, and transforming growth factor β1 (TGF-β1) have been investigated for promoting EMT. However, in the present study, the role of the sphingomyelin synthase 1 (SMS1) in TGF-β1-induced EMT development was investigated. Firstly, bioinformatics analysis demonstrated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 35 publications
2
15
0
Order By: Relevance
“…EMT plays a vital role in tumor metastasis as is evident by the upregulated expression of N-cadherin and Vimentin, while the expression level of E-cadherin is downregulated (34). TGF-β/Smad signaling pathway is an important driver in promoting the EMT process via activating the canonical pathway as with Smad family members or non-canonical signaling molecules such as Rho kinase (35,36). TGF-β1-induced EMT has been implicated in diabetic kidney diseases, fibrosis phenotype and tumor cell Following serum starvation for 24 h, stable NRP1-silenced A549 and H226 cells were treated with or without TGF-β1 (5 ng/ml) for 48 h. The expression of p-Smad3, Smad3, Snail, MMP2, MMP9, N-cadherin, Vimentin was analyzed by western blot analysis.…”
Section: Discussionmentioning
confidence: 99%
“…EMT plays a vital role in tumor metastasis as is evident by the upregulated expression of N-cadherin and Vimentin, while the expression level of E-cadherin is downregulated (34). TGF-β/Smad signaling pathway is an important driver in promoting the EMT process via activating the canonical pathway as with Smad family members or non-canonical signaling molecules such as Rho kinase (35,36). TGF-β1-induced EMT has been implicated in diabetic kidney diseases, fibrosis phenotype and tumor cell Following serum starvation for 24 h, stable NRP1-silenced A549 and H226 cells were treated with or without TGF-β1 (5 ng/ml) for 48 h. The expression of p-Smad3, Smad3, Snail, MMP2, MMP9, N-cadherin, Vimentin was analyzed by western blot analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the overexpression of SMS1-inhibited EMT induced by TGFβ1 and coincides with the upregulation of E-cadherin and downregulation of vimentin [155]. Another study indicated that SMS1 blocks EMT via repressing the expression of TGFβR1 and SMAD2 phosphorylation [155]. Overall, these findings imply that sphingolipids play important roles in EMT induced by TGFβ, and a deeper understanding of the mechanisms by which sphingolipids regulate cancer cell signaling and metastasis will be beneficial to improve cancer treatment.…”
Section: Lipid Metabolism In Tgfβ-induced Emtmentioning
confidence: 93%
“…The decreased expression of SMS1 was found during TGFβ1induced EMT in the MDA-MB-231 cell line. In contrast, the overexpression of SMS1-inhibited EMT induced by TGFβ1 and coincides with the upregulation of E-cadherin and downregulation of vimentin [155]. Another study indicated that SMS1 blocks EMT via repressing the expression of TGFβR1 and SMAD2 phosphorylation [155].…”
Section: Lipid Metabolism In Tgfβ-induced Emtmentioning
confidence: 97%
“…EMT plays a vital role in tumor metastasis, accompanied by the up-regulated expression of N-cadherin and Vimentin, meanwhile the expression level of E-cadherin is down-regulated [31]. TGFβ/Smad signaling pathway is an important driver in promoting EMT process via activating canonical pathway like Smad family members or non-canonical signaling molecules like Rho kinase [32,33]. TGF-β1induced EMT has been implicated in diabetic kidney diseases, fibrosis phenotype and tumor cell metastasis [34][35][36].…”
Section: Discussionmentioning
confidence: 99%